2021
DOI: 10.1021/acsnano.1c01814
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchically Hollow Microfibers as a Scalable and Effective Thermal Insulating Cooler for Buildings

Abstract: Daytime passive radiative cooling is a promising electricity-free pathway for cooling terrestrial buildings. Current research interest in this cooling strategy mainly lies in tailoring the optical spectra of materials for strong thermal emission and high solar reflection. However, environmental heat gain poses a crucial challenge to building cooling at subambient temperatures. Herein, we devise a scalable thermal insulating cooler (TIC) consisting of hierarchically hollow microfibers as the building envelope t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
112
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(114 citation statements)
references
References 39 publications
2
112
0
Order By: Relevance
“…As a result, the aerogel achieved 13 °C below ambient cooling performance around solar noon. Another approach demonstrated that radiative cooler consisting of hierarchically hollow microfibers achieved high passive cooling performance (9 °C subambient) in the summer (Figure 7c), [70] wherein hierarchically hollow microfibers with nanostructures are an efficient light scattering medium and thermal insulator, providing strong solar reflection (94%) and IR thermal emission (0.94). Simultaneously, the hollow microfiber structure with ultralow thermal conductivity (i.e., 0.014 W m −1 K −1 ) restricted heat transfer between the cooler and its surrounding environment.…”
Section: Thermal Managementmentioning
confidence: 99%
“…As a result, the aerogel achieved 13 °C below ambient cooling performance around solar noon. Another approach demonstrated that radiative cooler consisting of hierarchically hollow microfibers achieved high passive cooling performance (9 °C subambient) in the summer (Figure 7c), [70] wherein hierarchically hollow microfibers with nanostructures are an efficient light scattering medium and thermal insulator, providing strong solar reflection (94%) and IR thermal emission (0.94). Simultaneously, the hollow microfiber structure with ultralow thermal conductivity (i.e., 0.014 W m −1 K −1 ) restricted heat transfer between the cooler and its surrounding environment.…”
Section: Thermal Managementmentioning
confidence: 99%
“…The hierarchical micro- and nanostructures with mesopores of sizes broadly distributed 3–20 nm (Figs. 1 d and S9) were responsible for the excellent sunlight scattering by the composite aerogel [ 30 , 70 ]. Considering that the solar intensity varies with the wavelength, the solar intensity weighted reflectance, , was calculated by Eq.…”
Section: Resultsmentioning
confidence: 99%
“…With this well-established concept, people developed different types of white cooling roof to improve indoor comfort and save on energy consumed by air conditioning. 39,40 However, in cooler regions with seasonal conditions, dark roofs are more popular [Fig. 1(b)].…”
Section: Criteria Of Spectral Selectivity For Radiative Coolingmentioning
confidence: 99%